Cameroon : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Extension of Arrangement, Waiver of Performance Criterion, and Extension of Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Overall, the program's macroeconomic targets have been broadly met. The program embodies a renewed emphasis on the non-oil revenue mobilization effort and continuation of a prudent expenditure stance. Reversing the deterioration of the financial operations of the public companies and the utilities is critical. The key objective is strengthening fiscal transparency. Executive Directors welcome the government's commitment to move forward with the implementation of structural reforms. Close and sustained monitoring, and enhanced coordination within the government, will be critical to the successful implementation of the program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Government Policy; International Agreements and Observance; International Organizations; Monetary Policy; Provision and Effects Of Welfare Program